Anti-PD-1 and Anti-CTLA-4 Therapies in Cancer: Mechanisms of Action, Efficacy, and Limitations - Seidel, Judith A.; Otsuka, Atsushi; Kabashima, Kenji (Frontiers in Oncology, 2018)
Melanoma, a skin cancer associated with high mortality rates, is highly radio- and chemotherapy resistant but can also be very immunogenic. These circumstances have led to a recent surge in research into therapies aiming to boost anti-tumor immune responses in cancer patients. Among these immunotherapies, neutralizing antibodies targeting the immune checkpoints CTLA-4 and PD-1 are being hailed as particularly successful. These antibodies have resulted in dramatic improvements in disease outcome and are now clinically approved in many countries. However, the majority of advanced stage melanoma patients do not respond or will relapse, and the hunt for the “magic bullet” to treat the disease continues. The following review will examine the mechanisms of action and the limitations of anti-PD-1/PD-L1 and anti-CTLA-4 antibodies, the two types of checkpoint inhibitors currently available to patients, and further explore the future avenues of their use in melanoma and other cancers.